2012
DOI: 10.1002/jbt.21409
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of toxicological pathways in TM3 leydig cell lines treated with Ethane dimethanesulfonate

Abstract: Ethane dimethanesulfonate (EDS), a well-known alkylating agent, selectively destroys Leydig cells. To clarify the molecular pathways underlying EDS action on Leydig cells, we analyzed gene expression profiles of an EDS-treated TM3 Leydig cell line. In this study, we analyzed the representative canonical pathways and toxicity pathways/gene lists using the Ingenuity Pathways Analysis program. In TM3 cells, 677 and 6756 genes were identified as being up- or downregulated after 3 and 24 h EDS treatments, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The EDS was provided by Professor Yuanqiang Zhang (Department of Human Anatomy, Histology and Embryology, The Fourth Military Medical University, China). According to the previous methods, EDS was dissolved in dimethyl sulfoxide (DMSO)/sterile water (1 : 3, v/v) [ 23 – 25 ]. Afterwards, the primary isolated SLCs were seeded into a 6-well plate and 0, 0.5, 0.75, and 1.0 mg/mL EDS (final concentration) were added to the culture solution, respectively [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The EDS was provided by Professor Yuanqiang Zhang (Department of Human Anatomy, Histology and Embryology, The Fourth Military Medical University, China). According to the previous methods, EDS was dissolved in dimethyl sulfoxide (DMSO)/sterile water (1 : 3, v/v) [ 23 – 25 ]. Afterwards, the primary isolated SLCs were seeded into a 6-well plate and 0, 0.5, 0.75, and 1.0 mg/mL EDS (final concentration) were added to the culture solution, respectively [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, EDS could eliminate differentiated LCs in pigs, which was accompanied with a decreased expression of CYP17A1, whereas the expression of PDGFRα did not change. The molecular pathway mechanisms underlying EDS action on LCs were related to intracellular glutathione (Kelce and Zirkin, 1993), activation of the Fas receptor (Taylor et al, 1999), oxidative stress (Lee et al, 2012), involvement of Bcl-2 family members (Taylor et al, 1998), or alkylation of proteins (Rommerts et al, 1985). In this study, we first uncovered that miR-205 was also involved in the process of EDS to eliminate differentiated LCs.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to being efficient in whole animal models, in vitro approaches using EDS on different Leydig cell lines have revealed that EDS is similarly effective as in vivo approaches. Although cell death was triggered in EDS-treated rat (H540) and mouse (MA-10 and TM3) Leydig cell lines, the differential sensitivity to EDS was maintained, with rat Leydig cell lines being more sensitive to EDS than the mouse cell lines ( Rommerts et al, 2004 , King et al, 1998 , Lee et al, 2012 , Li et al, 1822 ). These studies also highlighted some of the pathways that are affected by EDS treatment causing Leydig cell death.…”
Section: Introductionmentioning
confidence: 99%
“…As revealed by in vivo approaches and studies using Leydig cell lines, EDS invariably leads to Leydig cell death mainly by apoptosis involving the caspase signaling pathway ( Teerds and Rijntjes, 2007 , Rommerts et al, 2004 , King et al, 1998 ). There is also evidence that oxidative stress might trigger these events leading to apoptosis ( Lee et al, 2012 ). However, before apoptosis is triggered, there is a significant decrease in steroidogenesis and loss of steroidogenic function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation